1988
DOI: 10.1111/j.1365-2125.1988.tb03344.x
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic and natriuretic effects of nifedipine in healthy persons.

Abstract: 1 We have studied the diuretic and natriuretic effects and the tubular site of action of nifedipine using free water clearance (CH20) and lithium clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…We found that the natriuretic effect after felodipine treatment tended to be more pronounced than that after placebo, but this difference between felodipine treatment and placebo was not significant. This tendency is in accordance with other acute studies in healthy subjects [6,7,[10][11][12][13][14][15][16] in which calcium antagonists belonging to the dihydropyridine class have a natriuretic and diuretic effect. The mechanisms underlying these effects are presumed to be direct effects on the kidney, promoting decreased reabsorption of sodium in the tubules [8,10,13,14].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that the natriuretic effect after felodipine treatment tended to be more pronounced than that after placebo, but this difference between felodipine treatment and placebo was not significant. This tendency is in accordance with other acute studies in healthy subjects [6,7,[10][11][12][13][14][15][16] in which calcium antagonists belonging to the dihydropyridine class have a natriuretic and diuretic effect. The mechanisms underlying these effects are presumed to be direct effects on the kidney, promoting decreased reabsorption of sodium in the tubules [8,10,13,14].…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with our findings where BP was significantly reduced and HR was significantly increased by felodipine treatment. Vasodilatation and BP reduction would cause salt and water retention, but natriuretic and diuretic effects of calcium channel blockers prevent these side effects [6][7][8][9][10][11][12][13][14][15][16]. We found that the natriuretic effect after felodipine treatment tended to be more pronounced than that after placebo, but this difference between felodipine treatment and placebo was not significant.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It has also been reported that CCBs, especially those of the dihydropyridine class, increase urinary sodium and water excretion, partly by decreasing proximal tubular sodium reabsorption. 21,22 In addition, CCBs have been proven to be effective in preventing arteriosclerosis, 23,24 whereas diuretics can damage the sugar/fat metabolism system, 25,26 a possible factor in exacerbation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%